Ferroan Dolomitization by Seawater Interaction with Mafic Igneous Dikes and Carbonate Host Rock at the Latemar Platform, Dolomites, Italy: Numerical Modeling of Spatial, Temporal, and Temperature Data - K. Blomme; S. J. Fowler; P. Bachaud; F. H. Nader; A. Michel; R. Swennen (Geofluids)
Numerous publications address the petrogenesis of the partially dolomitized Latemar carbonate platform, Italy. A common factor is interpretation of geochemical data in terms of heating via regional igneous activity that provided kinetically favorable conditions for replacement dolomitization. New field, petrographic, XRD, and geochemical data demonstrate a spatial, temporal, and geochemical link between replacement dolomite and local mafic igneous dikes that pervasively intrude the platform. Dikes are dominated by strongly altered plagioclase and clinopyroxene. Significantly, where ferroan dolomite is present, it borders dikes. We hypothesize that seawater interacted with mafic minerals, causing Fe enrichment in the fluid that subsequently participated in dolomitization. This hypothesis was tested numerically through thermodynamic (MELTS, Arxim-GEM) and reactive flow (Arxim-LMA) simulations. Results confirm that seawater becomes Fe-enriched during interaction with clinopyroxene (diopside-hedenbergite) and plagioclase (anorthite-albite-orthoclase) solid solutions. Reaction of modified seawater with limestone causes ferroan and nonferroan replacement dolomitization. Dolomite quantities are strongly influenced by temperature. At 40 to 80°C, ferroan dolomite proportions decrease with increasing temperature, indicating that Latemar dolomitization likely occurred at lower temperatures. This relationship between igneous dikes and dolomitization may have general significance due to the widespread association of carbonates with rifting-related igneous environments.